Penerapan Nilai Karakter Peduli Lingkungan Melalui Program Bank Sampah Oleh Aisyiyah - Harits Abdul Manaf; Deka Setiawan; Erik Aditia Ismaya (Jurnal Prakarsa Paedagogia, 2020)
This study aims to determine Aisyiyah's role in implementing the character of environmental care in Kedungsari Village, Kudus. This study used descriptive qualitative research. The subjects of this study were members of the Asyiyah organization and elementary school children. Simultaneously, the object under review is a waste bank managed by the Aisyiyah Organization in Kedungsari Village, Kudus. This study uses interview data collection techniques, observation, and documentation. Data analysis in this study used data analysis techniques in this study using interactive model analysis techniques. From the results of Process Aisyiyah, researchers' observations in applying the character of caring for the environment in the village of Kedungsari conveyed through recitation, farmer groups, and waste banks. Environmental care activities at the waste bank are carried out every 2-4 weeks. The process of Aisyiyah's members in implementing the character of caring for the environment in the family environment is the participation of mothers in the following coaching and their families also getting guidance from their mothers at home